Cost-Effectiveness of Telemedicine in Remote Orthopedic Consultations: Randomized Controlled Trial - Buvik, Astrid Synnøve; Bergmo, Trine Strand; Bugge, Einar; Småbrekke, Arvid; Wilsgaard, Tom; Olsen, Jan Abel (Journal of Medical Internet Research, 2019)
The following article, Buvik, A.S., Bergmo, T.S., Bugge, E., Småbrekke, A., Wilsgaard, T. & Olsen, J.A. (2019). Cost-Effectiveness of Telemedicine in Remote Orthopedic Consultations: Randomized Controlled Trial. Journal of Medical Internet Research, 21 (2), can be accessed at https://doi.org/10.2196/11330 . Background : Telemedicine consultations using real-time videoconferencing has the potential to improve access and quality of care, avoid patient travels, and reduce health care costs. Objective : The aim of this study was to examine the cost-effectiveness of an orthopedic videoconferencing service between the University Hospital of North Norway and a regional medical center in a remote community located 148 km away. Methods : An economic evaluation based on a randomized controlled trial of 389 patients (559 consultations) referred to the hospital for an orthopedic outpatient consultation was conducted. The intervention group (199 patients) was randomized to receive video-assisted remote orthopedic consultations (302 consultations), while the control group (190 patients) received standard care in outpatient consultation at the hospital (257 consultations). A societal perspective was adopted for calculating costs. Health outcomes were measured as quality-adjusted life years (QALYs) gained. Resource use and health outcomes were collected alongside the trial at baseline and at 12 months follow-up using questionnaires, patient charts, and consultation records. These were valued using externally collected data on unit costs and QALY weights. An extended sensitivity analysis was conducted to address the robustness of the results. Results : This study showed that using videoconferencing for orthopedic consultations in the remote clinic costs less than standard outpatient consultations at the specialist hospital, as long as the total number of patient consultations exceeds 151 per year. For a total workload of 300 consultations per year, the annual cost savings amounted to €18,616. If costs were calculated from ...